Correlation of Basic Science Process Skills and Learning Outcomes of High and Low Level Students In Junior High School 35 Padang - Eldyana Rahayu Putri; Helendra Helendra; Indra Hartanto; Yuni Ahda (ATRIUM PENDIDIKAN BIOLOGI, 2019)
Science process skill is one of the important thing that students should have within natural science. Teacher must recognize their students’ process skills in providing learning. The purpose of this study to determine correlation between basic science process skill of grade 7th students in Junior High School 35 Padang and their cognitive domain. The sample set consisted of 136 students. This study focus to determine correlation of basic process science skills in 6 categories, there are: observed, prediction, measurement, classification, conclusion and communication with cognitive domain. Descriptive method used in this research with students’ worksheet based on basic science process skill as the instrument of measurement students’  science process skill and test as  measurement cognitive domain. The correlation level between basic science process skill and cognitive domain shown by rs=0,43, it is indicate that basic science process skill have the positive and significant correlation with student’s cognitive domain. The correlation level between basic science process skills and cognitive domain of high level student shown by rs=0,43, this value indicate that basic science process skill have the positive and significant correlation with high level students’ cognitive domain. The last correlation between basic science process skill and cognitive domain of low level student with rs=0,21, it is indicate that basic science process skill have not significant correlation with low student’s cognitive domain.